Crystallization and preliminary X-ray diffraction studies of an L-amino-acid oxidase from Lachesis muta venom - Ullah, Anwar [UNESP]; Masood, Rehana [UNESP]; Spencer, Patrick Jack; Murakami, Mario Tyago; Arni, Raghuvir Krishnaswamy [UNESP] (Wiley-Blackwell, 2014)
Snake-venom proteins form multi-component defence systems by the recruitment and rapid evolution of nonvenomous proteins and hence serve as model systems to understand the structural modifications that result in toxicity. l-Amino-acid oxidases (LAAOs) are encountered in a number of snake venoms and have been implicated in the inhibition of platelet aggregation, cytotoxicity, haemolysis, apoptosis and haemorrhage. An l-amino-acid oxidase from Lachesis muta venom has been purified and crystallized. The crystals belonged to space group P2(1), with unit-cell parameters a = 66.05, b = 79.41, c= 100.52 angstrom, beta = 96.55 degrees. The asymmetric unit contained two molecules and the structure has been determined and partially refined at 3.0 angstrom resolution.